Detection of ≥1 Mb microdeletions and microduplications in a single cell using custom oligonucleotide arrays - Bi, Weimin; Breman, Amy; Shaw, Chad A.; Stankiewicz, Pawel; Gambin, Tomasz; Lu, Xinyan; Cheung, Sau Wai; Jackson, Laird G.; Lupski, James R.; den Veyver, Ignatia B. Van; Beaudet, Arthur L. (Prenatal diagnosis, 2012)
ABSTRACT Objective High resolution detection of genomic copy number abnormalities in a single cell is relevant to preimplantation genetic diagnosis and potentially to noninvasive prenatal diagnosis. Our objective is to develop a reliable array comparative genomic hybridization (CGH) platform to detect genomic imbalances as small as ~1 Mb in a single cell. Methods We empirically optimized the conditions for oligonucleotide‐based array CGH using single cells from multiple lymphoblastoid cell lines with known copy number abnormalities. To improve resolution, we designed custom arrays with high density probes covering clinically relevant genomic regions. Results The detection of megabase‐sized copy number variations (CNVs) in a single cell was influenced by the number of probes clustered in the interrogated region. Using our custom array, we reproducibly detected multiple chromosome abnormalities including trisomy 21, a 1.2 Mb Williams syndrome deletion, and a 1.3 Mb CMT1A duplication. Replicate analyses yielded consistent results. Conclusion Aneuploidy and genomic imbalances with CNVs as small as 1.2 Mb in a single cell are detectable by array CGH using arrays with high‐density coverage in the targeted regions. This approach has the potential to be applied for preimplantation genetic diagnosis to detect aneuploidy and common microdeletion/duplication syndromes and for noninvasive prenatal diagnosis if single fetal cells can be isolated. © 2012 John Wiley & Sons, Ltd.